2019
DOI: 10.1098/rspa.2019.0098
|View full text |Cite
|
Sign up to set email alerts
|

Silicon isotopes in Arctic and sub-Arctic glacial meltwaters: the role of subglacial weathering in the silicon cycle

Abstract: Glacial environments play an important role in high-latitude marine nutrient cycling, potentially contributing significant fluxes of silicon (Si) to the polar oceans, either as dissolved silicon (DSi) or as dissolvable amorphous silica (ASi). Silicon is a key nutrient in promoting marine primary productivity, contributing to atmospheric CO 2 removal. We present the current understanding of Si cycling in glacial systems, focusing on the Si isotope (δ 30 Si) compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(59 citation statements)
references
References 137 publications
(326 reference statements)
4
55
0
Order By: Relevance
“…Furthermore, glaciers were sampled at different stages of hydrological development. As discussed previously by Hatton et al (2019b), our 'spot sampling' approach may make potential signals difficult to identify and/or interpret due to their being taken out of the hydrological context of the site. Future efforts might find very different patterns and relationships with hydrochemical variables if samples are taken throughout different points in the year (Sheik et al, 2015;Dubnick et al, 2017a) or over a greater selection of sites.…”
Section: Relationships With Meltwater Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, glaciers were sampled at different stages of hydrological development. As discussed previously by Hatton et al (2019b), our 'spot sampling' approach may make potential signals difficult to identify and/or interpret due to their being taken out of the hydrological context of the site. Future efforts might find very different patterns and relationships with hydrochemical variables if samples are taken throughout different points in the year (Sheik et al, 2015;Dubnick et al, 2017a) or over a greater selection of sites.…”
Section: Relationships With Meltwater Characteristicsmentioning
confidence: 99%
“…While recent progress has been made in determining factors that control the magnitude of these biogeochemical fluxes, important clues into solute generation and the operation of the subglacial drainage system may be uncovered through the investigation of more qualitative characteristics of these exports. For example, past work has successfully shown that chemical signatures of dissolved organic matter Lawson et al, 2014;Dubnick et al, 2017b) and elemental isotopes Hatton et al, 2019b) are related to the hydrological and lithological characteristics of the glacial environment.…”
mentioning
confidence: 99%
“…Leverett Glacier (Lawson et al, 2014;Hawkings et al, 2015Hawkings et al, , 2016Hatton et al, 2019). These data span 4 months of continuously monitored bulk meltwater discharge (approximately the start of May to late August), which comprised the majority of the annual water flux (>75%), and daily samples for bulk meltwater ion chemistry over periods exceeding 2 months.…”
Section: Data Sources and Chemical Weathering Ratesmentioning
confidence: 99%
“…This increase is induced by the stronger slowdown of the North Atlantic deep circulation as a consequence of a stronger AMOC weakening. Moreover, the subpycnocline nutrient enrichment may be underestimated because our model system does not account for the effect of biologically relevant substances transported into the ocean by meltwater and iceberg calving due to microbial activity and hydrolysis reactions at the interface between land ice and the bedrock (such as dissolved iron, silicate and nitrogen; Bhatia et al, 2013;Duprat et al, 2016;Wadham et al, 2016;Hatton et al, 2019). Part of this additional nutrient input to the upper ocean would be consumed by primary producers and exported to deeper levels.…”
Section: Discussionmentioning
confidence: 99%
“…A schematic of the ocean grid and coupling domain is shown, e.g., in M19. Simulated physical and biogeochemical conditions on the NWES have been evaluated in various studies employing MPIOM/HAMOCC in coupled and uncoupled modes (Gröger et al, 2013;Mathis et al, 2015Mathis et al, , 2018Mathis et al, , 2019Pätsch et al, 2017;Hátún et al, 2017).…”
Section: Model Descriptionmentioning
confidence: 99%